Emotional Association with a Brand: A Link that Lasts in Consumers’ Memory Through Experience - Rawat, Jyoti (Indian Journal of Marketing, 2014)
Experience is that element which resides in the human mind and heart for a lifetime. Whenever the chapters of memories open, emotions are evoked, narrating whether the incident experienced was pleasurable or not. The purpose of this paper was to provide today’s marketers with an outlook on how experiences provided by products and services can entangle customers into emotional association with brands. The study also examined the effect of customers’ emotional association with a brand on satisfaction. The review of literature identified growing evidence of effect of product dimensions on customers’ emotional association with a brand. This paper has shown empirically how emotions primarily work on building customers’ emotional association with a brand.